Formulation and evaluation of CFC free inhalers for beclomethasone dipropionate (Brazilian Journal of Pharmaceutical Sciences, 2013)
Beclomethasone dipropionate CFC free inhalation formulations were developed with a view to treat asthma prophylactically. Dry powder inhalers (DPI) for beclomethasone dipropionate were prepared with different grades of lactose monohydrate. The influence of carrier and overages on performance of DPI was studied. Metered dose inhalers (MDI) with HFA based propellants were formulated with various doses, overages and different concentrations of alcohol. Formulated DPI and MDI were evaluated for various official and unofficial quality control tests. The influence of over doses on valve delivery, effect of overages on emitted dose and influence of alcohol on spray pattern from MDI were studied. The better fine particle fraction and emitted dose were obtained from the DPI formulated with 10:90 ratio of fine lactose: coarse lactose and with 20% w/w overages. The studies on MDI revealed that the 15% of overdoses are required for effective valve delivery and 20% overages are required for 100% drug delivery. 5-10%v/v alcohol was found to be preferable to get optimum emitted dose and fine particle fraction.